Language, Multilingualism and Education: The Interplay - Singal, Pooja (Voices of Teachers and Teacher Educators, 2018)
This Paper titled ‘Languages, Multilingualism and Education: explores the role of language in teaching learning situation. She has highlighted the fact that language learning should be embedded in the socio-cultural environment of the child and multilingualism should be used as a resource to bridge the gap between home language and the school language. She has also highlighted the fact that literacy originates from the oral language of the child and in the absence of the child’s voice it is not possible.